Relationship between emotional intelligence and academic achievement in emerging adults: a systematic review - Hanafi, Zahyah; Noor, Farukh (Human Resource Management Academic Research Society, 2016)
Emotional intelligence (EI), distinct as a cross-section of integrated emotional and social capabilities and skills that regulate how successfully people recognize and express their emotions, recognize others feelings and relate with them, and handle with daily stresses or pressures, effectively.The key purpose of this article is to systematically review the relationship between emotional intelligence and academic achievement in emerging adults (18-25 years old) by reviewing five widely used emotional intelligence (EI) measurements (EQ-I, ECI, TEIQue, MSCIT & WLEIS).The Google Scholar, Science Direct (Elsevier), ERIC, Scopus, and Web of science have been searched for relevant articles in English. After, thorough literature search, 786 articles have been identified. After exclusion of duplicates, title and abstract review, 46 articles have been read in full and out of this, 26 are considered for systematic review, comprising 8885 participants. Eight articles have used ability based measures of emotional intelligence (MSCIT, & WLEIS) and eighteen have used self-reported EI measures (EQ-I, ECI & TEIQue).Thirteen studies have reported a significant positive relationship between emotional intelligence (EI) and academic achievement (AA), two studies demonstrate that the relationship between EI and AA is strong, but it is indirect, two studies have found an insignificant but negative association and two studies demonstrates no relationship between EI and AA. Moreover, according to the result of seven studies, some EI components have been found significant in their relationship with AA. Subsequently, the relationship between EI and AA is supported by this systematic review. The results provide a base for a research intended at determining the relationship between emotional intelligence and academic achievement in emerging adulthood.